The Development Process of the Ecological Education in Independent Kazakhstan - Aigul, Primbetova; Gaukhar, Baltabayeva (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Today, the world community understands that one of the main reasons for the emergence of the global ecological crisis is the low education level, including the ecological one. On the 21st century threshold, the individual's ecological development is becoming a priority and a meaning-forming factor in state education policy. In many ways, it acts not only as a means of preserving nature but also of human civilization as a whole. This study recommends theorizing and establishing ecological education among learners. The future teacher needs to connect diverse thoughts about ecology and attempt to understand effective practices to cultivate a space of reflection for students and devise effective ways and methodologies to foster ecological education skills thought among student learners. The purpose of the present study was to collect and analyze environmental education undertaken with various subjects. For systematic analysis, selected databases and journals were analyzed across pre-determined criteria. The close examination resulted in 11 studies reporting the effects of the interventions (e.g., hands-on practices, field trip activities) and 4 studies reporting participants' views on the effects of the interventions in general. Later, these studies were subjected to content analysis to present the trends and to synthesize the common findings of the selected studies. The techniques and instructions used as the intervention in these selected studies were observed to contribute to the development of participants' gains associated with knowledge of the environment and nature, perception of nature, environmental effect, responsible environment behaviors, and conception and understanding of science.